Improving the differentiation of closely related males by RMplex analysis of 30 Y-STRs with high mutation rates. (May 2022) - Neuhuber, Franz; Dunkelmann, Bettina; Grießner, Ines; Helm, Katharina; Kayser, Manfred; Ralf, Arwin
Abstract: The discovery of rapidly mutating (RM) Y-STRs started to move the field of forensic Y-STR analysis from male lineage identification towards male individual identification. Previously, the forensic value of RM Y-STRs for differentiating male relatives was limited due to the modest number of 13 identified RM Y-STRs. Recently, new RM Y-STRs were discovered, with strong expectations for significantly improving male relative differentiation; however, empirical evidence is missing yet. More recently, the genotyping method RMplex for efficiently analyzing 30 Y-STRs with high mutation rates, including all 26 currently known RM Y-STRs, was introduced. Here, we applied RMplex as well as the current state-of-the-art commercial Y-STR kit: Yfiler™ Plus PCR Amplification kit, to several hundreds of DNA-confirmed father-son pairs. Newly established estimates confirmed the high mutation rates of novel and previous RM Y-STRs. By combining current with previous data, we provide updated consensus estimates of mutation rates for all 49 Y-STRs targeted with both methods. Based on RMplex, 42% of 499 father-son pairs were differentiated, while 14% of 530 pairs based on Yfiler™ Plus, and 48% of 499 pairs based on both methods combined. Regarding brothers, RMplex also clearly outperformed Yfiler™ Plus, with differentiation rates of 62% and 33%, respectively. By combining both methods 72.9% of the brothers showed at least one mutation. For unrelated males, both methods achieved a discrimination capacity of 99.8% and a haplotype diversity of 0.999991, since all males had different haplotypes, except for two, perhaps indicating a hidden paternal relationship. Overall, this study underlines the value of RM Y-STRs in general and RMplex in particular for differentiating male relatives highly relevant in forensic genetics. It provides the first empirical evidence on the high value of RMplex for differentiating close male relatives, which for father-son pairs was almost 60% higher than with the initial set of 13 RM Y-STRs and three times higher than with Yfiler™ Plus. Based on our results from closely related males, we expect RMplex to also improve the differentiation of more distantly related males significantly, which needs empirical demonstration in future studies. We encourage the forensic community to apply RMplex in all forensic cases where a match with a commercial Y-STR kit was obtained between the male suspect and the evidence material, or to solely use RMplex in such cases, aiming to find out if the male suspect or any of his male paternal relatives left the evidence material at the crime scene. Highlights: Confirmation of high mutation rates of recently discovered novel RM Y-STRs. First empirical father-son and brother differentiation rates for RMplex Y-STR set. Direct comparison of male relative differentiation by RMplex and Yfiler™ Plus. Father-son differentiation was 42% with RMplex, while only 14% with Yfiler™ Plus. Both methods differentiate all unrelated males except for two individuals.